The "Lyings" of a Woman: Male-Male Incest in Leviticus 18.22? - Lings, K. (Theology & sexuality, 2009)
This article offers a philological/literary analysis of a short biblical text in the book of Leviticus. Whenever discussions arise on the subject of homosexuality in the Bible, Lev. 18.22 is quoted. Most modern translations present this text as self-explanatory, which contrasts with the opacity of the original. The ambiguities embedded in the Hebrew wording have received limited attention. Put differently, Bible readers have not been invited to appreciate the internal logic of the text. Perhaps Lev. 18.22 does not prohibit all erotic expression between men. The overall context seems to indicate that the scope of this verse is far more restricted. If the text is analysed and translated carefully, there are reasons to believe that Lev. 18.22 is proscribing incest between male family members.